Extraction and separation of thorium and rare earths from nitrate medium with p‐phosphorylated calixarene. Issue 10 (25th February 2013) - Lu, Youcai; Bi, Yanfeng; Bai, Yan; Liao, Wuping
Abstract Background Thorium is a natural radioactive element which is often associated in different minerals with rare earth elements (REs). In order to satisfy application for nuclear fuel, thorium should be separated from REs and other elements. Calixarene derivatives have been proved to be excellent extractants towards thorium and REs. In this study, a p‐phosphorylated calixarene derivative was applied for extraction and separation of thorium and REs. Results p‐phosphorylated calix[4]arene, 5, 11, 17, 23‐tetra(diethoxyphosphoryl)‐ 25, 26, 27, 28‐tetrapropyloxy‐calix[4]arene (L), exhibits good selectivity towards thorium which is extracted into the organic phase as Th(NO3)4·3 L. The thermodynamic functions, ΔH, ΔG, and ΔS have been calculated as 5.55 kJ mol−1, −57.28 kJ mol−1 and 210.84 J mol−1 K−1, respectively. The salting‐out agents (NaNO3 and KNO3) can weaken the separation of Th and Yb but barely affects the separation of Th and La or Gd. Conclusion The extraction of thorium with the calixarene derivative occurs with a neutral extraction mechanism and the extraction reaction of thorium is an endothermic process. This ligand exhibits high extraction ability towards thorium over a wide range of acidity while the extraction of REs changes more with the solution acidity. Added salts can affect the separation of thorium and REs. This ligand may be used to separate thorium from REs under appropriate conditions. © 2013 Society of Chemical Industry